HIV and Hepatitis C–Coinfected Patients Have Lower Low‐Density Lipoprotein Cholesterol Despite Higher Proprotein Convertase Subtilisin Kexin 9 (PCSK9): An Apparent "PCSK9–Lipid Paradox". Issue 5 (May 2016) - Kohli, Payal; Ganz, Peter; Ma, Yifei; Scherzer, Rebecca; Hur, Sophia; Weigel, Bernard; Grunfeld, Carl; Deeks, Steven; Wasserman, Scott; Scott, Rob; Hsue, Priscilla Y.
Abstract : Background: Proprotein convertase subtilisin kexin 9 (PCSK9) inhibitors reduce low‐density lipoprotein cholesterol (LDL‐C) and improve outcomes in the general population. HIV‐infected individuals are at increased risk for cardiovascular events and have high rates of dyslipidemia and hepatitis C virus (HCV) coinfection, making PCSK9 inhibition a potentially attractive therapy. Methods and Results: We studied 567 participants from a clinic‐based cohort to compare PCSK9 levels in patients with HIV/HCV coinfection (n=110) with those with HIV infection alone (n=385) and with uninfected controls (n=72). The mean age was 49 years, and the median LDL‐C level was 100 mg/dL (IQR 77–124 mg/dL); 21% were taking statins. The 3 groups had similar rates of traditional risk factors. Total cholesterol, LDL‐C, and high‐density lipoprotein cholesterol levels were lower in coinfected patients compared with controls ( P <0.001). PCSK9 was 21% higher in HIV/HCV‐coinfected patients versus controls (95% CI 9–34%, P <0.001) and 11% higher in coinfected individuals versus those with HIV infection alone (95% CI 3–20%, P =0.008). After adjustment for cardiovascular risk factors, HIV/HCV coinfection remained significantly associated with 20% higher PCSK9 levels versus controls (95% CI 8–33%, P =0.001). Interleukin‐6 levels increased in a stepwise fashion from controls (lowest) to HIV‐infected to HIV/HCV‐coinfected individuals (highest) and correlated with PCSK9 ( r =0.11, P =0.018). Conclusions: Despite having lower LDL‐C, circulating PCSK9 levels were increased in patients coinfected with HIV and HCV in parallel with elevations in the inflammatory, proatherogenic cytokine interleukin‐6. Clinical trials should be conducted to determine the efficacy of targeted PCSK9 inhibition in the setting of HIV/HCV coinfection.